Risk of Deep Vein Thrombosis Following Laparoscopic Rectosigmoid Cancer Resection in Chinese Patients - Hester Yui-Shan Cheung (Asian Journal of Surgery, 2008)
The aim of this study was to evaluate the incidence of postoperative deep vein thrombosis (DVT) in Chinese patients who underwent laparoscopic resection of rectal or sigmoid cancer in the absence of thromboprophylaxis. METHODS: Patients with adenocarcinoma of the sigmoid colon or rectum scheduled for laparoscopic resection were recruited. Neither chemoprophylaxis nor mechanical methods against DVT were employed. They were scheduled to have routine duplex ultrasound of both lower limbs perioperatively. RESULTS: In a 12-month period, 50 patients were recruited. Postoperative DVT occurred in 19 (38%) patients. None needed anticoagulation. Complete resolution of the thrombus was noted in 10 (53%) patients 12 weeks after operation, and in six patients 36 weeks after operation. Female sex was identified as being associated with a higher incidence of DVT. Age, smoking, preoperative neoadjuvant chemoirradiation, preoperative metastasis, duration of operation, conversion and postoperative complications did not appear to be risk factors for DVT. CONCLUSION: The incidence of asymptomatic calf vein DVT is relatively high after laparoscopic resection for rectosigmoid cancers in the Chinese population. However, complete resolution occurred without the use of anticoagulant therapy in the majority of cases. It is thus difficult to advocate the routine use of anticoagulant prophylaxis.